Thiamine Deficiency in People with Obesity (P18-060-19). (13th June 2019) - Costello, Elizabeth; Kerns, Jennifer
Abstract: Objectives: Thiamine (vitamin B1) and other micronutrient deficiencies are commonly observed after bariatric surgery. However, there is evidence that patients with obesity may be deficient in thiamine even before surgery, possibly due to metabolic changes following recent weight loss or decreased intake through dietary restriction. Type II diabetes may also adversely affect thiamine absorption and increase urinary thiamine losses, placing patients with this condition at increased risk of deficiency. The purpose of this research is to (1) determine the prevalence of thiamine deficiency in patients at a bariatric surgery clinic and compare this across type II diabetes status, race, and gender; and (2) determine the relationship between recent weight loss and thiamine deficiency. Methods: This is a retrospective observational study of patients with obesity who were evaluated at the preoperative bariatric surgery clinic at the Washington, DC VA Medical Center between January 1, 2012 and April 1, 2018. Patients who had prior bariatric surgery, current or recent history of alcohol abuse, current use of diuretics or vitamin supplements, or for whom no thiamine test was ordered were excluded. All patients had a BMI of 31.7–49.0 kg/m 2 . Thiamine deficiency was defined as a test value below the reference range. Weight data were collected at the initial evaluation and up to four months prior. Results: Of 155 clinic patients, 107 met all inclusion criteria. Thiamine deficiency was found in 36 (33.6%) patients. Chi-square tests did not show any differences in prevalence between patients with type II diabetes and those without, or by gender or race. Preliminary logistic regression analyses indicated that the odds of thiamine deficiency were 14% higher per % increase in recent weight loss (OR = 1.14, 95% CI: 1.01–1.29). Conclusions: Approximately one third of those evaluated at the bariatric surgery clinic were found to have a test result indicating thiamine deficiency. This suggests that people with obesity, especially those engaging in weight loss efforts, may benefit from additional nutritional screening. Funding Sources: None.